(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Lignin is a natural polymer characterized by its ability to absorb ultraviolet rays and antibacterial properties. Thanks to nano size, nanolignin deposited on the fabric surface does not cause colour change, even though the lignin is originally dark. As a functional polymer it can be used as a natural UV barrier and antibacterial agent in finishing process of protective textiles. The paper describes the study on the improvement of nanoparticle fixation on the lignocellulosic fabric surface by the introduction of a binding agent in the finishing technology. Several binding agents with nanolignin solution were applied to the linen fabric and non-woven by padding method. Effectiveness of textile covering by functional nanoparticles was evaluated by UPF tests after ten washing cycles and abrasion tests. The best nanolignin coating on the linen fabric surface durability was obtained for application of acrylic dispersion as a binding agent. The FTIR (Fourier Transform Infrared) spectroscopy was applied for additional evaluation of linen fabrics covered by lignin nanoparticles.